2014
DOI: 10.1002/2013jb010451
|View full text |Cite
|
Sign up to set email alerts
|

Modeling deformation induced by seasonal variations of continental water in the Himalaya region: Sensitivity to Earth elastic structure

Abstract: Strong seasonal variations of horizontal and vertical positions are observed on GPS time series from stations located in Nepal, India, and Tibet (China). We show that this geodetic deformation can be explained by seasonal variations of continental water storage driven by the monsoon. For this purpose, we use satellite data from the Gravity Recovery and Climate Experiment to determine the time evolution of surface loading. We compute the expected geodetic deformation assuming a perfectly elastic Earth model. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 50 publications
5
131
0
Order By: Relevance
“…GPS position time series in Nepal and in the southern Tibetan Plateau suffer from strong seasonal variations due to hydrological loading, especially in the vertical and north components (e.g., Bettinelli et al, ; Chanard et al, ; Fu & Freymueller, ). The annual peak‐to‐peak amplitudes of the loading deformation in the vertical components can reach 20 mm, which is well recorded both by CGPS and Gravity Recovery and Climate Experiment (GRACE) data.…”
Section: Gps Data and Transient Postseismic Displacementsmentioning
confidence: 99%
“…GPS position time series in Nepal and in the southern Tibetan Plateau suffer from strong seasonal variations due to hydrological loading, especially in the vertical and north components (e.g., Bettinelli et al, ; Chanard et al, ; Fu & Freymueller, ). The annual peak‐to‐peak amplitudes of the loading deformation in the vertical components can reach 20 mm, which is well recorded both by CGPS and Gravity Recovery and Climate Experiment (GRACE) data.…”
Section: Gps Data and Transient Postseismic Displacementsmentioning
confidence: 99%
“…There are other factors, including surface hydrology in particular. Previous studies have indeed shown that geodetic strain in the Himalaya shows significant seasonal oscillations induced by variations of continental water storage (Bettinelli et al, 2008;Fu and Freymueller, 2012;Chanard et al, 2014). In this study, we correct the raw time series for the offsets related to the mainshock (2015.3121) and the largest aftershock of May 12, 2015 (2015.3603) which reached M w 7:2.…”
Section: Data and Signal Extractionmentioning
confidence: 99%
“…Another approach would be to predict the seasonal signal using measurements of surface load variations from the Gravity Recovery And Climate Experiment (GRACE) (Tapley et al, 2005). This approach has been proven successful (Bettinelli et al, 2008;Fu and Freymueller, 2012;Chanard et al, 2014) but it does not account well for spatial variability of the seasonal signal which can result from the limited (~400 km) spatial resolution of GRACE or local variations of the elastic response of the Earth due to sub-surface inhomogeneities or topographic effects. We therefore adopt another approach based directly on the ICA decomposition.…”
Section: Data and Signal Extractionmentioning
confidence: 99%
“…The annual signal is related to seasonnally pulsed surface and groundwater levels, which reflect surface response to the periodic hydrological loading as modeled in areas subject to similar variations (Tregoning et al, 2009;Chanard et al, 2014). The vertical component is particularly impacted ; the observed long-term trend is thus under influence of both tectonics and hydrology and is therefore not used in this study as it will be discussed in another article (Pastier et al, in prep).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%